STRATEGY FOR THE DEVELOPMENT OF VANILLA (Vanilla planifolia) FARMING IN THE KALAITI FARMER GROUP, KELAISI TENGAH VILLAGE, SOUTH ALOR DISTRICT, ALOR REGENCY - Maulaling, Yudhi Ariston; Hendrik, Ernantje; Chamdra, Santhy; Pellokila, Marthen Robinson (Undana Press, 2025)
This study was conducted in the Kalaiti Farmer Group, Kelaisi Tengah Village, South Alor District, Alor Regency, from November to December 2024. The objectives of this study were to describe vanilla farming in the Kalaiti Farmer Group, identify the internal and external factors related to vanilla farming, and formulate development strategies for vanilla farming in the study area. The study used descriptive qualitative and quantitative approaches. The respondents for internal-factor analysis consisted of 26 vanilla farmers selected using a census technique, while the external-factor respondents consisted of five key informants, namely village government representatives, an agricultural extension worker, and traders. Data were analyzed using IFAS, EFAS, and SWOT matrices. The results showed that the main internal strengths were skilled and experienced human resources, good road and transportation access, sound production-process planning, and complete farming equipment. The main weaknesses were limited production land, low use of social media for promotion, persistent pest and disease problems, and production dependence on weather conditions. External opportunities included relatively high vanilla prices, community participation and mutual cooperation, supportive government permits and regulations, and a relatively suitable production climate. External threats consisted of limited working capital, production security risks, limited extension support, and insufficient government assistance in the distribution of fertilizers and pesticides. The SWOT position was in Quadrant I, indicating an aggressive strategy. Therefore, vanilla farming development should prioritize SO strategies by maximizing existing strengths to exploit market and institutional opportunities.